Femur Mineral Density of Broilers with Femoral Degeneration Fed High Nutritional Density Diets - Paz, Ibiara Correia de Lima Almeida [UNESP]; Mendes, Ariel Antonio [UNESP]; Martins, M. R. F. B. [UNESP]; Fernandes, B. C. S.; Almeida, I. C. L.; Milbradt, E. L.; Balog, A.; Komiyama, C. M. (Soc Chilena Anatomia, 2009)
A study was carried out in the experimental facilities of FMVZ/UNESP-Botucatu, with the aim of following-up the development and the incidence of femoral degeneration (FD). A total of 305 one-day-old male broilers were housed in six pens of 5m(2) each. A completely randomized experimental design, with 3 treatments (T1-traditional nutritional density diet; T2-high nutritional density diet) of 3 replicates each was applied. Femoral head of the broilers were submitted to gross examination at 0, 7, 14, 21, 28, 35, and 42 days of aged. At 42 days of age, 60 birds (30 per treatment) were submitted to the Veterinary Hospital of FMVZ to determine bone mineral density by radiography. Birds were then sacrificed for gross examination of the legs, and FD scoring. Five legs per treatment within each FD score were submitted to computed tomography for femur head integrity and bone mineral density. Treatments did not influence FD incidence, and the first gross FD lesions appeared when birds were 28 days old. It was concluded that radiographic optical densitometry and computed tomography are efficient methods to evaluate femoral degeneration, and both techniques expressed the same profile. In addition, using radiographic optical densitometry and computed tomography, these results also allowed us to establish bone mineral density value ranges within each gross FD score. These finding may provide an excellent non-invasive tool to describe femoral degeneration.
Keywords: Femur; Mineral density; Broilers; Femoral degeneration; High nutritional density diets